DESIGN SPATIAL AND NON-SPATIAL DATA MODELLING BASED ON THE LADM STRUCTURE FOR LAND REGISTRY AND CADASTRAL SYSTEM IN TURKEY - Polat, Zeynel Abidin; Alkan, Mehmet (YILDIZ TECHNICAL UNIV, 2018)
In land administration, spatial data manegement plays the important role of defining physical characteristics of land parcels in an accurate and discernible manner. A complementary part of spatial data infrastructure (SDI) is an effective information infrastructure that serves as the backbone of the land administration system. The paper provides a framework that supports adoption of spatial data modelling based on Land Administration Domain Model (LADM) for Turkish Land Administration System (TLAS). For this purpose, a spatial and non-spatial data model based on LADM is designed concerning the single space units subject to condominium in Turkey. The proposed data model is more comprehensive, capable of organising a wider range of spatial data, and should facilitate wider exchange of land information. The model is unique because it can support a very wide range of spatial units. Furthermore, the model was developed to help establish a national spatial data infrastructure LADM-based. To conclude, the developed model is a standardised model that could be used for local and international exchange of spatial and non-spatial data concerning land administration matters.
Keywords: Spatial data infrastructure; spatial data modelling; LADM; Turkish Land Administration System; Engineering